EXPERIENCE OF FIFTEEN YEAR USE OF CYCLOSPORIN IN PAEDIATRIE RHEUMATOLOGY - E.I. Alexeeva; I.E. Shakhbazyan; S.I. Valieva; T.M. Bzarova; K.B. Isaeva; A.M. Chomakhidze; E.Yu. Afonina; O.S. Rozvadovskaya; V.Ya. El'yashevich; D.V. Apaeva ("Paediatrician" Publishers LLC, 2008)
A data of fifteen year experience of use of cyclosporin in treatment of systemic type of juvenile rheumatoid arthritis is presented in this article. Ciclosporin is high effective medication in mono therapy and combined with methotrexate. Cyclosporine in dose 3,5-4,5 mg/kg of bogy mass has no significant adverse events as in mono therapy, as in combination with methotrexate in moderate and high dose. Proper data of treatment of severe systemic type of rheumatoid arthritis in more then 100 children is presented.Key words: children, juvenile rheumatoid arthritis, cyclosporin, treatment.